The Effectiveness Of Narrative And Reality Approaches Group Counseling To Increase Self-Disclosure - Pramuaji, Krisan Andreas; Sugiyarto, DYP; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2022)
Self-disclosure as a process of presenting oneself is realized in the activities of sharing feeling, thoughts, and information with others. It is important for adolescents to develop an effective relationship, problem solving skills, obtain the meaning of a relationship, and have mental healthiness. Thus, the present study strived for identifying the effects of narrative approach group counseling and reality approach group counseling interventions to increase students’ self-disclosure. Here, 12 students were divided into two experimental groups. The groups were investigated using a comparison group pretest and multiple posttest design. Meanwhile, their data were collected using self-disclosure scale with 60 statement items. Based on mixed ANOVA test, both group counseling services have been effective to increase students’ self-disclosure. Further, the findings, implications, and limitations of this study are discussed in the discussion section.